General and domain‐specific cognitive reserve, mild cognitive impairment, and dementia risk in older women. Issue 1 (10th April 2019) - Petkus, Andrew J.; Resnick, Susan M.; Rapp, Stephen R.; Espeland, Mark A.; Gatz, Margaret; Widaman, Keith F.; Wang, Xinhui; Younan, Diana; Casanova, Ramon; Chui, Helena; Barnard, Ryan T.; Gaussoin, Sarah; et al.
Abstract: Introduction: In a geographically diverse sample of women, we asked whether cognitive reserve (CR) is best viewed as a general or cognitive domain‐specific construct and whether some cognitive reserve domains but not others exert protective effects on risk of developing mild cognitive impairment (MCI) or dementia. Methods: Estimates of general and domain‐specific CR were derived via variance decomposition in 972 cognitively intact women from the Women's Health Initiative Study of Cognitive Aging and Women's Health Memory Study Magnetic Resonance Imaging. Women were then followed up for 13 years. Results: General CR was the strongest predictor of reduced risk for both MCI and dementia, compared to domain‐specific CR measures. Verbal memory, figural memory, and spatial CR were independently protective of MCI, but only verbal memory was independently associated with reduced risk for dementia. Discussion: Cognitive reserve is a heterogenous construct with valid quantitative measures identifiable across different neuropsychological processes associated with MCI and dementia.